Agents of apocalypse epidemic disease in the colonial Philippines - De Bevoise, Ken 1943- (Princeton University Press, 1995)
As waves of epidemic disease swept the Philippines in the late nineteenth century, physicians in the islands began to fear that the indigenous population would be wiped out. Many Filipinos interpreted the contagions as a harbinger of the Biblical Apocalypse. Though the direst forebodings did not come to pass, Philippine morbidity and mortality rates were the world's highest during the period 1883-1903. In Agents of Apocalypse, Ken De Bevoise bypasses the simplistic conclusion that Spanish and American colonialism in the Philippines caused the epidemics. Instead, he explains that those "mourning years" resulted from a conjunction of demographic, economic, technological, cultural, and political processes that had been building for centuries. Throughout the book, the author highlights the complexity of cause and effect, which among other things accounts for the unintended consequences and tragic irony that characterize this history. On another level, the book is an ecology of human actions. De Bevoise uses the Philippine experience as a case study to explore the extent to which humans participate in creating their diseases. He interprets the archival record with conceptual guidance from the health sciences to set the nineteenth-century epidemics in a historical framework that shows people interacting with, rather than acting within, their total environment. Emphasizing the role of human actions in clearing the way for epidemic disease, he concludes that we are the primary agents of apocalypse. Readers from fields as diverse as Spanish, American, and Philippine history, medical anthropology, colonialism, international relations, Asian studies, and ecology will benefit from De Bevoise's insights into the interdynamics of historical processes that connect humans and their diseases.